SYSTEMATIC REVIEW GAMBARAN PENGETAHUAN IBU TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP KEJADIAN KARIES GIGI PADA ANAK PRASEKOLAH - Kirana Patrolina Sihombing; Ruben Putra Bhakti Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Mother's knowledge gives a very important and big role in directing, providing understanding, improving and providing facilities to children so that they are able to maintain their dental and oral health properly and correctly which will ultimately determine the incidence of dental caries in children. The purpose of this study was to obtain a description of the mother's knowledge about the maintenance of oral health on the incidence of dental caries in preschool-aged children. This research is a systematic review that examines 10 articles published between 2018-2021, obtained from searching the Google Scholar and Proquest databases using the keywords 'mothers and preschoolers' both in Indonesian and English. Based on the results of a review of 10 articles, it is known that 50% of mothers have a very good level of knowledge, and 60% of children have a high incidence of dental caries. This study concluded that the mother's level of knowledge about dental and oral health maintenance was in the good category (5 articles), the mother's level of knowledge was in the fair category (4 articles), and the status of the incidence of dental caries in preschool age children was in the high category (6 articles). Keywords: knowledge; dental caries; preschool children